Developing chitosan based green fungicides to control pre- and postharvest anthracnose of dragon fruit - Zahid, Noosheen (2014)
A study was conducted to develop an ecofriendly and sustainable fungicide based on submicron chitosan dispersions using low molecular weight chitosan and locally prepared chitosan. The physicochemical properties of both submicron dispersions were determined and their antimicrobial effect on Colletotrichum gloeosporioides was also investigated. The antifungal effect was further demonstrated by the production of fungal cell wall degrading enzymes and by the production of defence related enzymes in the plants along with the effect of submicron chitosan dispersions on the vegetative growth of plants. The effect of submicron chitosan dispersions on biochemical and physiological responses of dragon fruit during storage at 10 ± 2 °C and 80 ± 5% relative humidity for 28 days was also investigated. In vitro antifungal activity of submicron chitosan dispersions showed that low molecular weight chitosan has better antifungal properties than the locally prepared chitosan and therefore was selected for further studies. However, 600 nm droplets of 1.0% chitosan showed promising results in terms of suppressing mycelial growth (90.2%), conidial germination (93.1%) and reducing dry weight of mycelium (37.9%). Similarly, in vivo studies showed that the 600 nm droplets of 1.0% chitosan helped to reduce the disease incidence by up to 33.0 %. Beside the direct antifungal effect, this study suggests that the submicron chitosan dispersions enhanced host resistance through the production of defence related compounds, such as total phenols, peroxidase (PO), polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL) and also the activity of pathogenesis related proteins, such as β, 1-3 glucanase and chitinase. Treatments with submicron chitosan dispersions as 600 nm droplets of 1.0% chitosan showed more vigorous growth of plants as compared to the control. The submicron chitosan dispersions with 600 nm droplets of 1.0% chitosan helped to reduce the incidence of disease on fruit by up to 94% as compared to the control. The biochemical and physiological studies of dragon fruit after 28 days of storage showed that weight loss of the fruit treated with 600 nm droplets of 1.0% chitosan compared with the control reduced two fold but this was not significantly different from the conventional chitosan. The same trend was observed in all the parameters tested, including antioxidant activity. Control of disease using submicron chitosan dispersions has the potential to add market value to fresh produce. The findings from all the experiments showed that 600 nm droplets of 1.0% chitosan help to reduce anthracnose in the field and also during postharvest storage. Thus, 600 nm droplets of 1.0% chitosan could be used commercially in fields of dragon fruit as a green fungicide. Being non-toxic and biodegradable, chitosan has the potential to become an alternative to synthetic fungicides for protecting fruit crops and thus assisting sustainable agriculture.